2019
DOI: 10.1007/s00330-019-06033-x
|View full text |Cite
|
Sign up to set email alerts
|

Value of 3T craniocervical magnetic resonance imaging following nonfatal strangulation

Abstract: Objective The aims of this study were (1) to provide an overview of craniocervical magnetic resonance imaging (MR) findings following nonfatal strangulation (NFS), (2) to detect the time dependency of the presence of these findings, and (3) to explore the additional value of MR with regard to the forensic interpretation of NFS. Methodology All 633 victims of manual strangulation between October 2011 and March 2018 were examined, including the case history and external findings. Following written consent, 114 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 25 publications
1
40
1
Order By: Relevance
“…Only two studies reported the absence of subjective complaints showing that 17% of those 463 survivors reported no subjective symptoms following NFS. 22 26 Thus, the majority (83%) of strangulation survivors had some reported symptoms including neck pain, loss of consciousness and difficulty swallowing. On the other hand, absence of external injuries ranged from 17% to 93%, with the average being 44% of NFS survivors with no externally visible evidence of external injury.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies reported the absence of subjective complaints showing that 17% of those 463 survivors reported no subjective symptoms following NFS. 22 26 Thus, the majority (83%) of strangulation survivors had some reported symptoms including neck pain, loss of consciousness and difficulty swallowing. On the other hand, absence of external injuries ranged from 17% to 93%, with the average being 44% of NFS survivors with no externally visible evidence of external injury.…”
Section: Resultsmentioning
confidence: 99%
“… 25 This may have resulted in more cases where injuries were already visible receiving imaging and inflating the number of NFS injuries identified through MRI or CT scans. 22 26 Further, exercise of discretion for referral was identified as a problem even when decision guidelines were in place regarding imaging. For example, Bruguier et al showed that despite MRI eligibility criteria for NFS symptoms and injuries, only 11 of the 112 survivors over a 4-year period received an MRI following clinical assessment.…”
Section: Discussionmentioning
confidence: 99%
“…To exclude life-threatening complications such as carotid dissections [5], computed tomography (CT) with angiography is often applied in severe cases of NFS. The application of magnetic resonance imaging has been investigated with mixed results [6][7][8][9]. Overall, the need for sharply defined findings for the evaluation of NFS remains.…”
Section: Introductionmentioning
confidence: 99%
“…1,13,14 During the process of strangulation, neck injuries occur frequently, which can be visualized by computed tomography (CT), magnetic resonance imaging (MRI), or autopsy. 3,[15][16][17][18][19] According to these studies, intramuscular hemorrhages and subcutaneous bleeding are considered important indicators of severity. In those studies, MRI showed a significant value in detecting these injuries.…”
mentioning
confidence: 99%
“…In those studies, MRI showed a significant value in detecting these injuries. 4,15,19 However, postmortem imaging of ligature and manual strangulation has been described mainly in CT and x-ray, focusing on laryngeal lesions and subcutaneous hemorrhages. 20,21 Only a small case study analyzing MRI in fatal manual strangulation was presented by Yen et al 22 almost 15 years ago.…”
mentioning
confidence: 99%